2013
DOI: 10.1371/journal.pone.0083406
|View full text |Cite
|
Sign up to set email alerts
|

Dietary BMAA Exposure in an Amyotrophic Lateral Sclerosis Cluster from Southern France

Abstract: BackgroundDietary exposure to the cyanotoxin BMAA is suspected to be the cause of amyotrophic lateral sclerosis in the Western Pacific Islands. In Europe and North America, this toxin has been identified in the marine environment of amyotrophic lateral sclerosis clusters but, to date, only few dietary exposures have been described.ObjectivesWe aimed at identifying cluster(s) of amyotrophic lateral sclerosis in the Hérault district, a coastal district from Southern France, and to search, in the identified area(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(89 citation statements)
references
References 34 publications
2
84
1
Order By: Relevance
“…In mussels and oysters from Thau lagoon, France, BMAA, DAB and AEG have independently been detected by two groups at similar levels (Masseret et al, 2013;Reveillon et al, 2014). However, the distribution of BMAA in different organs of filter-feeding bivalves has not been studied so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mussels and oysters from Thau lagoon, France, BMAA, DAB and AEG have independently been detected by two groups at similar levels (Masseret et al, 2013;Reveillon et al, 2014). However, the distribution of BMAA in different organs of filter-feeding bivalves has not been studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…As cyanobacteria had been considered to be the most likely source of marine-derived BMAA, and had been suggested as a source of BMAA in Thau lagoon in a previous study (Masseret et al, 2013), we screened four strains of Synechococcus sp., previously isolated from Thau lagoon. Furthermore, emblematic protists isolated from this lagoon and available to this study included Ostreococcus tauri, and two strains of Alexandrium catenella.…”
Section: Introductionmentioning
confidence: 99%
“…N-β-methylamino-l-alanine (BMAA) is a natural non-protein amino acid that accumulates through food webs and eventually appears as a contaminant in some human diets (Cox et al 2003;Murch et al 2004a;Banack et al 2006;Banack and Murch 2009;Jonasson et al 2010;Brandt et al 2010;Masseret et al 2013;Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…A study in France investigated an ALS cluster near a lagoon that supplied oysters and mussels to the local population. The authors demonstrated that the shellfish were contaminated with BMAA, but also remarked that there was intensive chemical-based agriculture in the region [77]. Interestingly, cyanobacteria have been found to be remarkably resistant to glyphosate [78,79], and this could contribute to the recent record-setting algal blooms in the Great Lakes region, where glyphosate is extensively used on genetically modified (GM) RoundupReady crops [80].…”
Section: Bmaa and Als In Guammentioning
confidence: 99%